Management of hepatic hydrothorax and effect on length of stay, mortality, cost, and 30‐day hospital readmission. Issue 4 (12th September 2019) - Sobotka, Lindsay A; Spitzer, Carleen; Hinton, Alice; Michaels, Anthony; Hanje, A James; Mumtaz, Khalid; Conteh, Lanla F
Abstract: Background and Aim: Cirrhosis‐related complications are associated with high inpatient mortality, cost, and length of stay. There is a lack of multi‐centered studies on interventions for hepatic hydrothorax and its impact on patient outcomes. The aim of this study was to determine the effect of performing thoracentesis for hepatic hydrothorax on hospital length of stay, mortality, cost, and 30‐day readmission. Methods: A retrospective analysis of the Nationwide Inpatient Sample between 2002 and 2013 and Nationwide Readmission Database during 2013 was performed including patients with a primary diagnosis of hydrothorax or pleural effusion and a secondary diagnosis of cirrhosis based on International Classification of Disease 9 codes. Univariate and multivariate analyses were performed to determine the effect of thoracentesis on patient outcomes during their hospital stay. Results: Of the 37 443 patients included from the Nationwide Inpatient Sample, 26 889 (72%) patients underwent thoracentesis. Thoracentesis was associated with a longer length of stay (4.56 days, 95% confidence interval [CI]: 2.40–6.72) and higher total cost ($9449, 95% CI: 3706–15 191). There was no significant difference in inpatient mortality between patients who underwent thoracentesis compared with those who did not. Of the 2371 patients included from the Nationwide Readmission Database, 870 (33%) were readmitted within 30 days. Thoracentesis was not a predictor of readmission; however, transjugular intrahepatic portosystemic shunt (odds ratio: 4.89, 95% CI: 1.17–20.39) and length of stay (odds ratio: 1.02, 95% CI: 1.001–1.05) on index admission were predictors of readmission. Conclusion: When considering treatment for hepatic hydrothorax, many factors should contribute to determining the best intervention. While performing thoracentesis may provide immediate relief to symptomatic patients, it should not be considered a long‐term intervention given that it increases hospital cost, was associated with longer length of stays, and did not improve mortality.